Case Report: Bronchogenic Cyst in the Right Atrium of a Young Woman - Fukudome, Yuya; Hieda, Michinari; Masui, Shiho; Yokoyama, Taku; Futami, Shutaro; Moriyama, Shohei; Irie, Kei; Fukata, Mitsuhiro; Ushijima, Tomoki; Shiose, Akira; Akashi, Koichi (Frontiers in Cardiovascular Medicine, 2022)
A 31-year-old woman was referred for evaluation of a cardiac mass in the right atrium. Cardiac magnetic resonance imaging indicated the presence of a cystic mass with fluid accumulation in the right atrium. The mass was diagnosed as a cardiac cyst and was surgically removed. Pathological examination revealed that the cyst was an extremely rare bronchogenic cyst. Bronchogenic cysts are benign congenital cysts of primitive foregut origin that form in the mediastinum during embryonic development. There is a clinical dilemma surrounding the treatment plan for cardiac surgery or biopsy of the cardiac mass, especially in patients with rare cardiac cysts. The anatomical location of the cyst is related to various clinical symptoms and complications. In cases of indeterminate cardiac cysts, direct removal of the cyst without previous biopsy is of utmost importance.